2021
DOI: 10.1253/circrep.cr-20-0104
|View full text |Cite
|
Sign up to set email alerts
|

Mst1/2 Kinases Inhibitor, XMU-MP-1, Attenuates Angiotensin II-Induced Ascending Aortic Expansion in Hypercholesterolemic Mice

Abstract: Background: Ascending and abdominal aortic aneurysms (AAs) are asymptomatic, permanent dilations of the aorta with surgical intervention as the currently available therapy. Hippo-Yap signaling cascade plays a critical role in stem cell self-renewal, tissue regeneration and organ size control. By using XMU-MP-1, a pharmacological inhibitor of the key component of Hippo-Yap signaling, MST1/2, we examined the functional contribution of Hippo-Yap in the development of AAs in Angiotensin II (AngII)-infused hypercho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…XMU-MP-1 is the chemical probe widely being used to study the Hippo pathway. Several publications have described the cellular roles of MST1/2 in the Hippo pathway with XMU-MP-1, assuming the molecule can pharmacologically inhibit the function of MST1/2 [54,[57][58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…XMU-MP-1 is the chemical probe widely being used to study the Hippo pathway. Several publications have described the cellular roles of MST1/2 in the Hippo pathway with XMU-MP-1, assuming the molecule can pharmacologically inhibit the function of MST1/2 [54,[57][58][59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Jones et al showed that JCAD (Junctional Cadherin 5 Associated) regulates adhesion molecule expression and monocyte-EC adhesion by interacting with LATS2, which is a kinase in the Hippo pathway, in a LATS2dependent manner (152). However, the administration of an inhibitor of the Hippo kinase MST1/2 resulted in the attenuation of Angiotensin II-induced ascending arterial aneurysms without affecting aortic atherosclerotic plaque progression (158). Due to mouse models and the effects of exogenous inhibition, further direct investigation of the role of Hippo kinase in atherosclerosis is needed.…”
Section: Vascular Endothelial Cellsmentioning
confidence: 99%